Socialize the Biopore Modification and Utilization as a Composting Media and Disaster Mitigation Efforts in Blawi Village, Karangbinangun, Lamongan - Marsha Savira Agatha Putri; Nur Lathifah Syakbanah; Nur Azizah Affandy; Salwa Nabilah; Adisti Risma Putri Azzahra Arismaya (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Blawi is a village where geographically located near the Bengawan Solo River crosses Lamongan Regency. During the wet season, Blawi Village often experiences flooding, however the contrary during the dry season it often experiences drought. Thus, with the background of these problems, it is necessary to carry out outreach the “Socialization and Utilization of Biopori with modification of Giving Effective Microorganism 4 (EM4)